2016
DOI: 10.1007/s11419-016-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evaluation of synthetic cannabinoids identified as constituents of spice

Abstract: In recent years, many synthetic cannabinoid (CB) receptor agonists have appeared on the market as constituents of herbal incense mixtures known as “spice”. Contrary to the declared use, they are perorally consumed as a replacement for marijuana to get “high”. In many cases, detailed information on the physicochemical and pharmacological properties of the synthetic compounds found in spice preparations is lacking. We have now evaluated a large series of heterocyclic compounds, 1,3-disubstituted indole and 2-aza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 45 publications
7
126
0
2
Order By: Relevance
“…Upon analysis of these herbal mixtures, the synthetic cannabimimetics JWH-018 and CP 47,497-C8 were identified as the primary psychoactive components [1]. Since then, several structural classes of SCBs have quickly evolved and diversified to avoid forensic detection and legislative scheduling [1, 5]. Individual users have sought after SCBs to avoid detection in standardized drug testing as well as to achieve a more intense high than that associated with marijuana [3].…”
Section: Synthetic Cannabinoids (Scbs): Not Simply Fake Marijuanamentioning
confidence: 99%
See 1 more Smart Citation
“…Upon analysis of these herbal mixtures, the synthetic cannabimimetics JWH-018 and CP 47,497-C8 were identified as the primary psychoactive components [1]. Since then, several structural classes of SCBs have quickly evolved and diversified to avoid forensic detection and legislative scheduling [1, 5]. Individual users have sought after SCBs to avoid detection in standardized drug testing as well as to achieve a more intense high than that associated with marijuana [3].…”
Section: Synthetic Cannabinoids (Scbs): Not Simply Fake Marijuanamentioning
confidence: 99%
“…Aside from the major chemical classes of SCBs, including classical cannabinoids, cyclohexyl-substituted phenols, naphthoylindols, and benzoylindoles, newer SCB structures such as tetramethylcyclopropylindoles, adamantoylindoles, indazole carboximides and quinolinyl esters have been popularized in K2/Spice products [5, 23] (Figure 1). While these SCBs have been advertised as “synthetic marijuana,” when compared to Δ 9 -THC, they are structurally heterologous.…”
Section: History Of Emerging Scb Abuse and Progression Of Scb Structumentioning
confidence: 99%
“…Several research groups have reported diŠerentiations of structural isomers based on diŠerences in the fragment ions in full scan/ product ion scan mass spectra 6 12) . However, a group of SCs containing a ‰uorobenzyl group at the N-1 position, including N-(1-amino-3-methyl-1-oxobutan-2-yl)-1-(4-‰urobenzyl)-1H-indazole-3-carboxamide ( AB-FUBINACA ) 13,14) , N-( 1-amino-3,3-dimethyl-1-oxobutan-2-yl ) -1-( 4-‰urobenzyl ) -1H-indazole-3-carboxamide ( ADB-FUBINACA ) 14,15) , methyl 2-[ 1-( 4-‰uorobenzyl ) -1H-indazole-3-carboxamido ] -3-methylbutanoate ( FUB-AMB; AMB-FUBINACA) 16) , and N-(1-adamantyl)-1-(4-‰uorobenzyl ) -1H-indazole-3-carboxamide ( FUB-APINACA; FUB-AKB48 ) 17) , were di‹cult to distinguish from their ‰uorine positional isomers in both full scan and product ion scan mass spectra because few characteristic fragment ions were observed. Contributing to this challenge was the fact that the reference standards for the positional isomers were not readily available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Several drug addiction services have reported an increase in synthetic cannabis users reverting back to methamphetamine. Prosecutions under the Misuse of Drugs Act for possessing, supplying, administering, or dealing in methamphetamine and amphetamine have risen, 26 and methamphetamine seizures increased by more than nine times between 2013 and 2015. 32…”
Section: Effect On Public Safetymentioning
confidence: 99%
“…Many of the synthetic cannabinoid legal highs are assumed to be cannabinoid receptor agonists but a large proportion have mixed pharmacology. 26 The New Zealand Act permits approved licence holders to conduct scientific research with potential psychoactive substances, 27 although research organisations have to pay a substantial fee for this licence. At the time of writing there were "eight licences to research" listed on the government website, 28 four of which were to universities or crown owned organisations.…”
Section: Implications For Medical Researchmentioning
confidence: 99%